The preferences on choosing home financing among Malaysian in Kuala Lumpur / Mohd Shalem Mohd Zin - Mohd Zin, Mohd Shalem (Faculty of Business and Management, 2014)
In Malaysia, the financial institution are operates in dual banking system. The financial institution offer two forms of home financing method which are Islamic home financing and conventional home loan. Therefore, this study is about the preference on choosing home financing among Malaysian in Kuala Lumpur, whether they are more favor on Islamic or conventional type of financing. Thus, the ultimate aim of the study is to study relationship between bank reputation, financial benefit, influence and recommendation and home financing and also the most factors that influence Malaysian preference on choosing home financing. Primary data are collected using self-administered questionnaire. The questionnaire was designed in two sections, one consisting of demographic information and the second relating to the preference on choosing home financing. The samples comprised 100 respondents from employees in area Kuala Lumpur. The sampling procedure adopted in this research was convenience sampling. The findings show that all the bank reputation, financial benefit and influence and recommendation have positive relationship with home financing while bank reputation has the greatest impact on home financing and becomes the most factors among three independent variables. The analyses presented in this research can be used by Government as a guide to improve the policy or create new policy for home borrower. Besides, it also contributes to the financial institutions in designing effective strategies to attract the people in choosing home financing.